Perubahan Pola-Pola Perkawinan pada Masyarakat Lampung Saibatin - Ali Imron; Rinaldo Adi Pratama (Universitas Andalas, 2020)
This article discusses the marriage system that occurred in the Lampung Saibatin community. This study examines how the marriage system change based on their own needed. This study was an ethnography research that would be described qualitatively, this is intended because the concern of the research is the way of life of the Lampung Saibatin community. The results showed that the Lampung Saibatin marriage in the 1970s underwent a change from a very strong Bujujogh with patrilineal to a Semanda marriage system. Lampung Saibatin community develops a new marriage system using Semanda which is an influence of the Minangkabau people, this is done by Lampung Saibatin people because they are reluctant to be called a failed family or ”mupus”. This study sees that the changes that occur due to two vital elements are that emerge from within the Saibatin community itself which includes privilege and economy. Meanwhile, external factors are new cultures that come from other people, get a better education and government policy.